A Hybrid Query Scheme to Speed Up Queries in Unstructured Peer-to-Peer Networks. (5th August 2007) - Zhang, Zhan; Tang, Yong; Chen, Shigang; Jian, Ying
Abstract : Unstructured peer-to-peer networks have gained a lot of popularity due to their resilience to network dynamics. The core operation in such networks is to efficiently locate resources. However, existing query schemes, for example, flooding, random walks, and interest-based shortcut suffer various problems in reducing communication overhead and in shortening response time. In this paper, we study the possible problems in the existing approaches and propose a new hybrid query scheme, which mixes inter-cluster queries and intracluster queries. Specifically, the proposed scheme works by efficiently locating the clusters, sharing similar interests with intercluster queries, and then exhaustively searching the nodes in the found clusters with intracluster queries. To facilitate the scheme, we propose a clustering algorithm to cluster nodes that share similar interests, and a labeling algorithm to explicitly capture the clusters in the underlying overlays. As demonstrated by extensive simulations, our new query scheme can improve the system performance significantly by achieving a better tradeoff among communication overhead, response time, and ability to locate more resources.